Optimasi Pembagian Barang Alat Tulis Kantor Menggunakan Algoritme Genetika - Ardiansyah Setiajati; Imam Cholissodin; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays almost all companies need technology in helping business activities. Therefore information technology can help the company's activities in achieving its goals effectively and efficiently. Office stationery is one of the important supporting tools in running the operational functions of a company. Currently, office stationery management system in some companies or agencies are still done manually, so there is still often error information. Genetic algorithm is a population-based algorithm that can solve problems related to optimization with a very wide search space. Genetic algorithms can solve problems by providing a set of solutions and finding the most optimal solution. The chromosome representation consists of 801 genes comprising the sum of each item that each position can take. The optimal solution result is obtained on the test which is done 10 times using parameter that is the number of generation 2250, cr value 0,1, mr value 0,9, and population size 100, with fitness value equal to 7,288. However, there are still violations which is the number of some items that exceed the stock. Therefore, the solution is still not optimal.